The Efforts of Housewife to Improve Communication Patterns in the Family at Padang Lawas Regency, North Sumatera - Sudirman Sudirman; Inayati Hasni Nasution; Rosramadhana Rosramadhana (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The problem in this study is communication within the family, specifically between fathers and young women who are not well- established. The role of mothers who tend to be considered not to facilitate the occurrence of good communication patterns between fathers and young women in the family. This study aims to describe information about the pattern of communication that exists between fathers and young women in the family, then describe the role of mothers as communication facilitators in family and to find out the results of communication patterns between fathers and young women. The theory used about "The pattern of family communication proposed by McLeon and Chafee consists of a laissez-faire, protective, pluralistic and consensual pattern". This type of research uses a pre experimental design research design in the form of one group pre test-post test. The treatment given is in the form of counseling. Samples taken as many as 42 people. Data collection tool used is a questionnaire. Data analysis techniques using descriptive statistics and hypothesis testing (t-test). The results of descriptive statistical analysis and hypothesis testing (t- test) to determine whether there are changes before and after treatment. From the results of descriptive statistical formulas and hypothesis testing (t-test) obtained tcount = 41.496 while ttable = 1.682, then tcount = 41.496> ttable = 1.682. then the hypothesis is accepted. This proves that there is a change in the role of mothers as facilitators to improve family communication patterns in Siolip village, Barumun sub-district, Padang Lawas Regency.